Interiors of the Garbhagriha of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
The interiors of the garbhagriha (sanctum sanctorum) of the Chaunsath Yogini Temple are plain and minimally ornamented. It is square on plan with a trabeated ceiling. The temple is not actively used for worship now. But originally, it must have been dedicated to Goddess worship which can be speculated based on the pedestal which has the depiction of a goddess sculpture on its front side.